Physical activity for improving the symptoms of attention deficit hyperactivity disorder in children and adolescents - Parker, Jack (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the effects of physical activity interventions for children and adolescents aged 18 years or younger with a diagnosis of attention deficit hyperactivity disorder (ADHD).